2020
DOI: 10.1080/10410236.2020.1839202
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Message Effectiveness and Campaign-Targeted Beliefs: Evidence of Reciprocal Effects in Youth Tobacco Prevention

Abstract: Perceived message effectiveness (PE) has been widely used in campaign formative research and evaluation. The relationship between PE and actual message effectiveness (AE) is often assumed to be causal and unidirectional, but careful conceptualization and empirical testing of this and other causal possibilities are generally lacking. In this study, we investigated the potential reciprocity in the relationship between PE and AE in the context of a national youth tobacco education campaign. In so doing, we also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This finding is consistent with the existing literature. Zhao et al [ 32 ] found a significant positive relationship between exposure to The Real Cost campaign and PE. They also found a significant positive relationship between awareness of the truth ® campaign and PE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the existing literature. Zhao et al [ 32 ] found a significant positive relationship between exposure to The Real Cost campaign and PE. They also found a significant positive relationship between awareness of the truth ® campaign and PE [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [ 32 ] found a significant positive relationship between exposure to The Real Cost campaign and PE. They also found a significant positive relationship between awareness of the truth ® campaign and PE [ 32 ]. This finding is also consistent with previous studies that have shown higher receptivity to tobacco advertising with repeated exposure to these ads [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They completed a six-item perceived effectiveness scale associated with attitude and behavior change in previous studies by indicating if each video was worth remembering, attention-grabbing, powerful, informative, meaningful, and convincing. ( Davis et al, 2013 , Zhao et al, 2022 , Davis et al, 2017 , Alvaro et al, 2013 ) A perceived effectiveness score for each ad was calculated by averaging responses to the six questions. Participants also indicated if each video gave them hope that there is help for people who use meth, discouraged them from using meth, and if they trusted the ad.…”
Section: Methodsmentioning
confidence: 99%
“…Existing measures of PME tend to focus heavily on relatively brief persuasive messages in broad-reaching media, such as television/video advertisements or warnings on product packaging [ 18 , 19 ]. For example, PME has been a central research tool for developing and evaluating youth tobacco education campaigns sponsored by the US Food and Drug Administration (FDA) [ 12 , 20 , 21 ]. In these campaigns, the assessment of PME has almost exclusively focused on brief, simple, disparate educational messages (e.g., a 30-s PSA on dangerous chemicals in cigarette smoke).…”
Section: Perceived Effectivenessmentioning
confidence: 99%